Control interno de cuentas por pagar del año 2021 de la empresa Agrícola Agro Fértil Productos Químicos para el Campo S.A. de la parroquia Ricaurte, cantón Urdaneta. - Franco Jiménez, Cindy Lisbeth (2023)
The proper management of accounts payable is crucial for the economic and financial management of companies, especially in the agricultural sector. The lack of adequate management can generate additional expenses and late fees, which in turn could cause a cash shortage in the company and make financial planning difficult. The present case study focuses on analyzing the internal control of accounts payable of Agrícola Agro Fértil Productos Químicos para el Campo S.A. during the year 2021, with the aim of identifying weaknesses in the management process. The lack of control policies can lead to serious economic losses, making this process essential for financial planning. A mixed approach was used to analyze and collect quantitative and qualitative data on the company's accounts payable. A field investigation was conducted to obtain information directly from the company's legal representative through an interview. The results of the study show the need to improve internal control in the management of accounts payable and the handling of financial obligations to avoid additional financial costs and reduce its net profit margin.